(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The purpose of the study was to investigate the effect of artificial intelligence (AI) on advancing financial inclusion in Zimbabwean banks through AI credit scoring, chatbots, anomaly detection systems, and predictive analytics. The researchers used a mixed-methods research design which included data collection from 293 respondents who completed the questionnaire and 12 participants who came for the interview. Artificial intelligence (AI) technology enables loan processing by making financial products more accessible through its three main functions which are usability and safety in transactions and financial literacy training. The researchers found that organisations strongly supported AI systems for decision-making and fraud detection yet users still had concerns about how AI credit assessments and chatbot operates. AI adoption process faces critical obstacles which originate from four sources which are digital illiteracy, poor Internet access, excessive application costs and the rural-to-urban divide. Anomaly detection systems had the most significant impact on financial outcomes since they explain 62.3% of the outcome differences which AI technologies produce. The research found that AI functions as an essential instrument for advancing financial inclusion in Zimbabwe through its ability to enhance banking access and operational efficiency and secure banking services. The study recommended the establishment of more accessible AI systems for decision-making, providing digital literacy programme improvements through regulatory support, and creating special resources for communities that lack essential services.